Complications of Nonpermanent Facial Fillers: A Systematic Review. Issue 10 (22nd October 2021) - Oranges, Carlo M.; Brucato, Davide; Schaefer, Dirk J.; Kalbermatten, Daniel F.; Harder, Yves
Abstract : Background: A variety of complications after injection of nonpermanent fillers for facial rejuvenation have been reported so far. However, to date, the overall complication rate is still a matter of debate. The aim of this study was to perform a systematic review of literature to assess the type and severity of associated complications following injections in different anatomical regions of the face. Methods: The entire PubMed/Medline database was screened to identify case reports and clinical studies describing complications that have occurred after injection of nonpermanent fillers in the face. These complications have been reviewed and analyzed according to their occurrence in different anatomical regions of the face. Results: Forty-six articles including a total of 164 patients reported on a total of 436 complications during the time period between January 2003 and February 2020. The majority of the complications were reported after injections to the nose and the nasolabial fold (n = 230), the forehead and the eyebrows (n = 53), and the glabellar region (n = 36). Out of 436 complications, 163 have been classified as severe or permanent including skin necrosis (n = 46), loss of vision (n = 35), or encephalitis (n = 1), whereas 273 complications were classified as mild or transient, such as local edema (n = 74), skin erythema (n = 69), and filler migration (n = 2). The most severe complications were observed in treatments of nose, glabella, and forehead. Conclusions: Nonpermanent facial fillers are associated with rare but potentially severe complications. Severity and impact of complications depend on the anatomical region of the face and eventually require profound knowledge of facial anatomy.